PENGARUH MODEL CREATIVE PROBLEM SOLVING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SD NEGERI 84 SINGKAWANG - Nafia, Siti Ulya; Marhayani, Dina Anika; Mulyani, Sri (Universitas Islam Sumatera Utara, 2024)
This study aims to determine whether there are differences and the effect of using the Creative Problem Solving model assisted by learning videos for grade V students of SDN 84 Singkawang. The type of research used is quantitative research with the method of true experimental design with posstest-only control group design. The samples taken in the study were V-B class students totaling 24 students. Data collection techniques using essay question test techniques by containing indicators of problem solving ability. Data analysis techniques using t-test and effect size. The results of this study showed that: 1) there is a difference in problem solving skills between classes using the CPS model assisted by learning videos and classes using direct learning models, 2) the use of the CPS model has an effect, but not significant on students' problem solving skills with the results of the effect size of 0.60 and falls into moderate criteria.